A review on solid oxide fuel cell stack designs for intermediate temperatures - Shri Kumaran; Zuraida Awang Mat; Zulfirdaus Zakaria; Saiful Hasmady Abu Hassan; Yap, Boon Kar (Penerbit Universiti Kebangsaan Malaysia, 2020)
Solid oxide fuel cell (SOFC) has significant advantages of clean and quiet operation while providing a relatively high efficiency owing to enhanced reaction kinetics at high operating temperature. The high operating temperature of SOFC, typically around 800 – 1000°C helps to enable internal reforming of hydrocarbons and negate effects of impurities in small quantities in the fuel. However, this limits the application of SOFC only to stationary applications due to the long period needed to reach this temperature range. A high temperature operation is also not ideal in terms of cost reduction and long-term stability of the cell components. Hence, lowering the operating temperature of SOFC is crucial for reduction of cost production and commercialization, which enables SOFC to have a wider range of application areas inclusive of portable and mobile ones. Building a high-performance SOFC with small volume is essential as the underlying criteria for these small-scale portable applications. Therefore, careful design and fabrication methods of SOFC operating on intermediate temperatures with high power outputs need to be considered. The intermediate temperature operation of the fuel cell not only increases the overall lifespan of cell but also allows for longer operation with a lower degradation rate compared to high temperature operation. Furthermore, a modified intermediate temperature stack design can accommodate a wider range of applications compared to the tubular and planar stack designs. This paper reviews the development of SOFC stack designs aimed at intermediate temperature operation towards achieving high performance and the benefits of each design.